Readily available materials for rearing adult stage of the Mediterranean Fruit-fly Ceratitis capitata (Wied) (Diptera: Tephritidae) - Abugelal, O. A.; Al-Eian, S. A. (Al-Mukhtar Journal of Sciences, 1998)
Four adult diets readily available materials were tested for daily egg production , egg production / female and egg hatchability of the Mediterranean fruit - fly Ceratitis capitata (Wied). The colony was maintained under laboratory condition for six generations. Diets composed of date molasses and honey mixed with date flax are less expensive than enzymatic yeast hydrolyzate+sugar (control), of better physical properties and gave higher production of eggs.